Impact of dumping of wastewater from carbon washing on the physicochemical properties of the soil - Aquino Montoro, Josselyn Azucena; García Martínez, Geraldine Paola; García Reyes, Laura Valentina (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
The coal process is one of the most important activities in economic growth in the country, however, in recent years nature itself has given evidence that show the impacts on the soil due to mismanagement and lack of human awareness, such as deterioration and loss of fertility. Therefore, this study determined the physicochemical impacts on the organic layer of the soil caused by the dumping of wastewater from the carbon washing process in the surrounding soils to the washing plants, or direct sources of dumping. In this sense, and through a quantitative and qualitative study of wastewater, the presence of substances was determined by the near infrared spectrometer method, conductivity, pH with multiparameter, turbidity by the Nephelometer method and the Biological Oxygen Demand with the measurement of DBO BD 600. In the same way, for representative soil samples, pH, porosity, apparent density, saturation humidity was evaluated by the cylinder method of known volume, conductivity and organic matter empirically. The results showed the presence of heavy metals, pH from 3.45 to 8.64 within the acidity ranges, high values in heavy elements such as CA2 + in 23500 to 80 784 mg / kg of soil, demonstrating that it is a highly contaminated soil.